Pengaruh Insentif dan Komitmen Organisasi terhadap Niat Melakukan Whistleblowing - Widy Amelia Putri; Sany Dwita (Universitas Negeri Padang, 2022)
This study aims to examine the effect of incentives and organizational commitment to whistleblowing intentions. This type of research is classified as a quasi-experiment. The data in the study were collected by distributing online questionnaires using google form to 126 accounting students class 2018 at the Faculty of Economics, Universitas Negeri Padang. The data used in this study is primary data. The experimental design used is a 2x2 factorial design. The results of the study were obtained from the use of Analysis of Variance (ANOVA). This study resulted in two findings. First, the study results indicate that individuals will do whistleblowing if there is an incentive. second, organizational commitment does not affect the individual's intention to do whistleblowing.